Fewpal
+1 vote
984 views
in Mathematics by (160 points)
edited by
solve the following pair of linear equation by substitution method s-t=3,s÷3+t÷2=6

1 Answer

+2 votes
by (64.2k points)
selected by
 
Best answer

Solution: We have 

– = 3 ... (i)
s/3 + t/2 = 6 ... (ii)
From equation (i), we gets t + 3
Putting this value in equation (ii), we get
t+3/3 + t/2 = 6
2t + 6 + 3t = 36
5t = 30
t = 30/5 ... (iv)
Putting in equation (iii), we obtain
s = 9
∴ s = 9, t = 6

Welcome to Sarthaks eConnect: A unique platform where students can interact with teachers/experts/students to get solutions to their queries. Students (upto class 10+2) preparing for All Government Exams, CBSE Board Exam, ICSE Board Exam, State Board Exam, JEE (Mains+Advance) and NEET can ask questions from any subject and get quick answers by subject teachers/ experts/mentors/students.

Categories

...